2020
DOI: 10.1002/acr.24450
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Psychiatric Diagnosis and Treatment on Medication Adherence in Youth With Systemic Lupus Erythematosus

Abstract: Objective. Youth with systemic lupus erythematosus (SLE) experience high rates of psychiatric comorbidities, which may affect medication adherence. We undertook this study to examine the association between psychiatric disorders and hydroxychloroquine adherence and to determine whether psychiatric treatment modifies this association. Methods. We identified incident hydroxychloroquine users among youth with SLE (ages 10-24 years) using de-identified US commercial insurance claims in Optum Clinformatics Data Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Adults with SLE and psychiatric illness typically have worse disease control, educational achievement, and work productivity, [20][21][22] and youths with concurrent chronic medical and psychiatric illnesses are more likely to report poorer school performance, quality of life, and disease control. 5,18,22,23,24 In our study, adolescents with cSLE also commonly identified issues with education, adherence to treatment, sleep, and challenges at home. Less common were issues of body image and diet, substance use, safety concerns, and sexuality, although these were still identified in 15% to 20% of our patients.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Adults with SLE and psychiatric illness typically have worse disease control, educational achievement, and work productivity, [20][21][22] and youths with concurrent chronic medical and psychiatric illnesses are more likely to report poorer school performance, quality of life, and disease control. 5,18,22,23,24 In our study, adolescents with cSLE also commonly identified issues with education, adherence to treatment, sleep, and challenges at home. Less common were issues of body image and diet, substance use, safety concerns, and sexuality, although these were still identified in 15% to 20% of our patients.…”
Section: Discussionmentioning
confidence: 64%
“…[1][2][3] A recent study found that 20% of youth aged 10 to 24 years with SLE had a concurrent psychiatric diagnosis, the most common of which was depression. 18 Despite the knowledge that youth with cSLE have higher rates of mood disorders compared to the general population, they are often underdiagnosed and undertreated. 1,19 Although 50% of adolescents in our study had identified mood concerns during their adolescent medicine visits, only 29% had a psychiatric diagnosis, highlighting that many adolescents with cSLE struggle with mood even without a formal mood disorder diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of potential relevance is the association between depression and lower treatment adherence [ 25 , 26 , 27 , 28 ], a known driver for lupus flare and activity. This finding, however, lacks extensive confirmation or may be influenced by other factors such as ethnicity [ 29 , 30 , 31 , 32 ]. Therefore, evaluation of the frequency and determinants of mental disorders in different regions and clinical settings is important.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al 30 performed a retrospective cohort study through an online database (Clinformatics DataMart) of 873 cSLE patients (age 10–24) taking hydroxychloroquine to assess the exposure of a psychiatric diagnosis on treatment adherence and, pertinent to this review, examined the effect of psychotherapy utilization (defined in chart review as clinical treatment of at least 4 visits) on treatment adherence via MPR. This study received a lower evidence grade 3 as it lacked randomization, but had low risk of bias aside from that lack of randomization.…”
Section: Clinical Psychotherapymentioning
confidence: 99%